Sosialisasi Sistem Informasi Kontrasepsi Rasional (SIKONTRAS) Pada Warga Kelurahan Kerten, Laweyan, Solo - Ita Permatahati; Rahmad Ardhani (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
The need for education regarding the types of contraceptives will have an impact on increasing knowledge and choice of contraceptives in women. At the same time, adjustments to technological developments also need to be made, so the team designed a mobile web-based of Sistem Informasi Kontrasepsi Rasional (SIKONTRAS) which is intended for the wider community in ease of obtaining information related to contraceptives. This socialization activity resulted in two things, namely an increase in knowledge related to contraception and an increase in skills in using the SIKONTRAS Application resulting from the questionnaire at the point "The application is easy to use", out of 21 participants, 18 participants chose "strongly agree", so it can be said that the application is easy to use. use